Thermoradiative energy conversion in infrared interband cascade InAs/GaSb/AlInSb/GaSb type-II superlattice diodes - Md Toriqul Islam; Sheikh Alimur Razi; Nuha Ahmed Babikir; Jianjian Wang; Rui Q. Yang; John F. Klem; Jamie D. Phillips (APL Energy)
Thermoradiative energy conversion presents a means for the direct conversion of thermal energy through radiative transfer to a cold scene. However, much of the study of thermoradiative principles has been based on theory and simulations, with only sparse reports on the experimental demonstration of the concept. This work studies thermoradiative energy conversion in InAs/GaSb/AlInSb/GaSb type-II superlattice cascade devices. The devices exhibit a cutoff wavelength of 3.2 μm at 300 K, corresponding to a bandgap of 0.39 eV. Testing under a temperature-controlled chamber and scene demonstrates a maximum power density of 2.9 mW/m2 at a cell temperature of 121 °C. It is consistent with expected values for device operation limited by Shockley–Read–Hall non-radiative recombination. This result is a significant step in providing an experimental demonstration of thermoradiative energy conversion and a means to characterize cell performance, providing a foundation for further development to achieve practical values for power generation.